Is Mandatory Carbon Disclosure Associated With Real Carbon Performance: A Study of South African Companies Listed on JSE - NYAHUNA, Thomas; DOORASAMY, Mishelle; NOMLALA, Bomi (International Journal of Environmental, Sustainability, and Social Science, 2023)
With the increasing importance of carbon disclosure as a tool to reduce carbon emissions, the enduring question remains whether carbon disclosure reduces carbon emissions. This paper analyzes the rapport between "carbon disclosure and carbon performance" of 82 Johannesburg Stock Exchange (JSE) listed mining and manufacturing firms grounded on data released from 2010 to 2021. The environmental disclosure index is used in this study to quantify carbon disclosure, and the carbon intensity of the selected firms is used to gauge carbon performance. Using IBM SPSS Statistics 26, the study discovers that carbon disclosure (p< -0.023) is negatively associated with carbon performance. It means that an increase in carbon disclosure minimizes carbon performance. Additionally, the study finds that carbon disclosure improves financial performance proxied by return on assets. The findings strongly support King Code III and IV's position that companies can improve environmental and financial performance by extensively disclosing environmental impacts. In this case, carbon disclosure can act as an instrument to improve corporate sustainability and counteract climate change. In line with the research results, it is recommended that policymakers in South Africa promote and adopt policies that compel and regulate companies to disclose their environmental impacts.